234k views
1 vote
Let p=x^2+6p=x 2 +6p, equals, x, start superscript, 2, end superscript, plus, 6. Which equation is equivalent to (x^2+6)^2-21=4x^2+24(x 2 +6) 2 ?21=4x 2 +24left parenthesis, x, start superscript, 2, end superscript, plus, 6, right parenthesis, start superscript, 2, end superscript, minus, 21, equals, 4, x, start superscript, 2, end superscript, plus, 24 in terms of p ?

User Greg Weber
by
5.3k points

2 Answers

4 votes

Answer: p^2-4p-21=0

Explanation:

Did it on Khan :D

User Mike Davlantes
by
4.6k points
3 votes

Answer:

Explanation:

Given p = x²+6

We are to express (x²+6)-21 = 4x²+24 in terms of p

We need to rewrite the expression first

(x²+6)²-21 = 4x²+24

Factor out 4 from the right hand side;

(x²+6)²-21 = 4(x²+6)

Replace x²+6 with p

p²+21 = 4p

Collect like terms

p²-4p = -21

p²-4p+21= 0

Hence the required equation is p²-4p+21= 0

User Jagough
by
4.6k points